Alternate Level of Care: How Health Restructuring is Changing the Social Work Role - Sholtz, Erik Todd (My University, 2009)
Social workers who are employed in a medical environment function in a situation that presents unique challenges to the profession. Currently the medical field in general and hospital settings specifically are experiencing extreme pressure to modify the manner in which they provide services. One manifestation of the current pressures that especially affects hospital social workers is alternative level of care (ALC). This thesis will examine the interplay of contemporary pressures on healthcare organizations, and social workers' professional practices. I will explore hospital social workers' perceptions of the transformation of their roles resulting from the intersection of organization and professional expectations using ALC as a back drop.
Although previous research has examined this concern from a more theoretical approach, little attention has been paid to the day to day experiences of front line workers. This study, based on a focus group with hospital social workers; extends our understanding of the impact of organizational influences on the role social workers occupy within health care organizations.
The changes in social work practice were understood in a range of ways by the focus group participants. In the most positive framing, any changes that were acknowledged were seen to be "instrumental." At the same time, group participants identified many potentially problematic changes in the actual practice of social work associated with ALC. Focus group members provided some insights as to how organization influences impacted on social work's apparent change in focus and practice.
It is my contention based on this study that contemporary organizational influences fundamentally change the manner in which the profession operates. If these organizational pressures are left unchallenged, social workers risk losing the ability to serve either the individual or greater good, making moot the debate surrounding our most appropriate role.
Keywords: Social Work; Social Work